2022
DOI: 10.1001/jamanetworkopen.2022.29333
|View full text |Cite
|
Sign up to set email alerts
|

Risk Levels and Adverse Clinical Outcomes Among Patients With Nonvalvular Atrial Fibrillation Receiving Oral Anticoagulants

Abstract: IMPORTANCEThe CHA 2 DS 2 -VASc score (calculated as congestive heart failure, hypertension, age 75 years and older, diabetes, stroke or TIA, vascular disease, age 65 to 74 years, and sex category) is the standard for assessing risk of stroke and systemic embolism and includes age and thromboembolic history. To our knowledge, no studies have comprehensively evaluated safety and effectiveness outcomes among patients with nonvalvular atrial fibrillation receiving oral anticoagulants according to independent, cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
2
4
1
Order By: Relevance
“…This result was consistent with a previous study based on five large health claims databases in the United States, where 89.0% of patients were estimated to have a high-risk of stroke. 12 Similar demographic characteristics, including an average age of over 70 years old and a higher proportion of males, were observed in comparable investigations. 14,23 This study revealed a higher incidence of adverse clinical outcomes compared to previous studies and an increasing trend with higher CHA 2 DS 2 -VASc scores.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This result was consistent with a previous study based on five large health claims databases in the United States, where 89.0% of patients were estimated to have a high-risk of stroke. 12 Similar demographic characteristics, including an average age of over 70 years old and a higher proportion of males, were observed in comparable investigations. 14,23 This study revealed a higher incidence of adverse clinical outcomes compared to previous studies and an increasing trend with higher CHA 2 DS 2 -VASc scores.…”
Section: Discussionsupporting
confidence: 71%
“…The incidence of IS in Asian patients included in this study was notably higher across different CHA 2 DS 2 -VASc score categories compared to Western populations. 11,12 Additionally, the estimated incidence of IS in our study was higher than those reported in most prior studies involving Asian populations, highlighting a greater disease burden for the Chinese population. [13][14][15][16] We observed that the incidence of TIA and AE also increased with the CHA 2 DS 2 -VASc scores.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Lip and colleagues conducted a real-world observational analysis by combining 5 large US insurance claims data sets consisting of over 1.1 million patients with AF who received oral anticoagulation between January 2012 and June 2019. The most common stroke risk factor was hypertension (84.5%) followed by coronary artery disease (42.7%), diabetes (36.0%), and congestive heart failure (28.8%).…”
mentioning
confidence: 99%
“…While the analysis by Lip and colleagues largely validates the guideline-supported CHA 2 DS 2 -VASc risk score approach, it raises question as to how the score is applied. For instance, a man with a CHA 2 DS 2 -VASc score of 2 due to hypertension and diabetes is estimated to have a stroke or systemic incidence rate of only 0.56 events per 100 person-years, which is markedly lower than the estimated rate of major bleeding (2.17 events per 100 person-years).…”
mentioning
confidence: 99%